ANALISIS EFISIENSI PENGGUNAAN ALOKASI DANA DESA TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT KECAMATAN MATANGKULI KABUPATEN ACEH UTARA - Adrikal Muna; Hijri Juliansyah (LPPM UNIMAL, 2019)
This study aims to analyze the level of efficiency of the use of Village Fund Allocation for community economic empowerment in various villages in Matang Kuli District. This is quantitative research that uses primary data with data collection techniques using questionnaires. The analytical method used is the DEA method (Data envelopment analysis). The results showed that there were significant differences in efficiency between villages in Matangkuli District, namely CRS and VRS. The results of the CRS and VRS state that the Turquoise Mosque Village is more efficient than other villages as evidenced by the value of 1,000 (on the frontier line).